Pendukung Keputusan Dalam Peramalan Penjualan Ayam Broiler Dengan Metode Trend Moment Dan Simple Moving Average Pada CV. Merdeka Adi Perkasa - Kurniadi, Win (STMIK Budi Darma, 2018)
Forecasting is the approximate level of demand for one or more products over the coming periods. In forecasting the level of demand for no excess and no less the amount of broiler chicken stock based on sales in the past. Decision supporters are investigated to predict the number of requests using trend moment method and simple moving average method and measure the level of accuracy predict by means of mean absolute percentage error. With both methods, the result of the research showed that trend moment method obtained the highest mean absolute percentage error of 4,08% and the lowest was 36.12% while the moving average method obtained the highest mean absolute percentage error of 3.25% and the lowest was 23.12%.